Esej o rozstaniu. Pamięci Cezarego Wodzińskiego - Marczyńska, Julia (Civitas. Studia z filozofii polityki, 2016)
This is a metaphysical essay devoted to the phenomenon of parting. The author analyses two events that happened to the Russian poet Marina Tsvetaeva on 31 August 1941: parting with her life and parting with her son. A thorough analysis of the poet’s goodbye letter to her son, and in particular the handwritten underlining that is absent from reprints, sheds new light on why the great poet committed suicide. The main subject of discussion, however, remains the phenomenon of separation. The article is dedicated to the memory of Professor Cezary Wodziński, the supervisor of my doctoral dissertation, my teacher and friend. The methodology takes a phenomenological approach and linguistic analysis.